Application of multimedia user friendly e-lecture notes - Zeki, Akram M.; Rosdi, Iffah Nadhirah; Aszenan, Azliza (IIUM Press, 2015)
The International Islamic University Malaysia (IIUM) offers multitude of relevant programs from Foundation level to Bachelor degree level to cater for the different needs of potential students. The foundation program prepares the students to embark on higher level of study at bachelor degree level while the diploma program is designed for dual path, i.e. students pursuing bachelor degree and students embarking on different profession. The chapter discusses how to create a new web-based system for the university programs. This is to provide easiness in terms of selecting and combining one or more lecturers’ schedule and view it in one timetable. In addition it will facilitate managing the course repository and records of each faculty without merging with others faculty’s records.